2000
DOI: 10.1093/ajcn/71.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Taurine improves insulin sensitivity in the Otsuka Long-Evans Tokushima Fatty rat, a model of spontaneous type 2 diabetes

Abstract: Taurine effectively improves metabolism in OLETF rats by decreasing serum cholesterol and triacylglycerol, presumably via increased secretion of cholesterol into bile acid and decreased production of cholesterol because of increased nitric oxide production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
88
0
5

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(103 citation statements)
references
References 23 publications
10
88
0
5
Order By: Relevance
“…2B). This effect of taurine treatment is in agreement with some rodent studies that showed taurine administration attenuated the increase of blood glucose concentration during glucose tolerance testing [11][12][13][14][15][16][17] . In general, most glucose (>80%) is taken up by skeletal muscle 21) .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…2B). This effect of taurine treatment is in agreement with some rodent studies that showed taurine administration attenuated the increase of blood glucose concentration during glucose tolerance testing [11][12][13][14][15][16][17] . In general, most glucose (>80%) is taken up by skeletal muscle 21) .…”
Section: Discussionsupporting
confidence: 90%
“…Glycogen repletion in skeletal muscle after exercise is one of the major determinants of performance during subsequent exercise since higher pre-exercise glycogen content in skeletal muscle resulted in improving performance during both prolonged endurance and high-intensity intermittent exercise [2][3][4][5] . Some rodent studies have shown the possibility that taurine administration enhances glucose uptake in tissues [11][12][13][14][15][16][17] , which is one of the limiting factors for glycogen synthesis in skeletal muscle. Therefore, we hypothesized that taurine administration enhanced postexercise glycogen repletion in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anuradha and Balakrishnan (1999) found that adding taurine (2%) to the ad libitum drinking water of fructose-fed Wistar rats decreased the fructose-induced exaggerated glucose levels and hyperinsulinemia (Po0.05). The same observations were made by Nakaya et al (2000) when 5% taurine was added to the food of fructose-fed Otsuka Long Evans Tokushima Falty (OLETF) diabetic rats, resulting in less hyperglycemia and decreased insulin resistance. In a recent study by with fructose-fed insulin-resistant rats, an IVGTT showed an enhanced insulin action when a dose of taurine 2% w/w was added to drinking water.…”
Section: Introductionsupporting
confidence: 56%
“…We cannot Effect of taurine treatment on insulin secretion and action C Brøns et al exclude the possibility that this effect could have been found in the present study as well if diabetic subjects had been included. Several animal studies have shown that taurine has a beneficial effect on insulin sensitivity (Maturo & Kulakowski, 1988;Anuradha & Balakrishnan, 1999;Nakaya et al, 2000;. Human studies of type I and II diabetics have suggested that taurine has a glucose-lowering effect (Elizarova & Nedosugova, 1996;Franconi et al, 1996).…”
Section: Effect Of Taurine Treatment On Insulin Secretion and Action mentioning
confidence: 99%